1993
DOI: 10.1017/s0890037x00027755
|View full text |Cite
|
Sign up to set email alerts
|

Imazaquin Absorption, Translocation, and Metabolism in Flue-Cured Tobacco

Abstract: Absorption of14C-imazaquin by leaves of field-grown flue-cured tobacco was similar when applied to young seedlings immediately after transplanting or to plants 3 wk after transplanting. The distribution of14C in treated leaves indicated that 40% was absorbed, 54% remained in water extracts of leaf surfaces, and 6% was found in the epicuticular wax layer 8 d after treatment. Translocation of the herbicide from treated leaves to roots was very low (4 to 5%). In contrast, soil applications of imazaquin and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…and false-green kyllinga (K. gracillima L.) rapidly absorbed 14 C-trifloxysulfuron between 0 and 4 HAT, with an accumulation of 47% 14 Cherbicide after 96 h. Troxler et al (2003) observed that purple and yellow nutsedge quickly absorbed 14 C-trifloxysulfuron between 0 and 4 HAT and approximately 55% of applied after 96 h. Askew and Wilcut (2002) reported that cotton (Gossypium hirsutum L.), jimsonweed (Datura stramonium L.), peanut (Arachis hypogaea L.), and sicklepod [Senna obtusifolia (L.) Irwin and Barnaby] all rapidly absorbed 14 Ctrifloxysulfuron between 0 and 4 HAT, but total absorption after 72 h varied by species between 30 and 70%. By comparison, tobacco absorbed 40% of applied 14 C-imazaquin 8 d after treatment (Walls et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and false-green kyllinga (K. gracillima L.) rapidly absorbed 14 C-trifloxysulfuron between 0 and 4 HAT, with an accumulation of 47% 14 Cherbicide after 96 h. Troxler et al (2003) observed that purple and yellow nutsedge quickly absorbed 14 C-trifloxysulfuron between 0 and 4 HAT and approximately 55% of applied after 96 h. Askew and Wilcut (2002) reported that cotton (Gossypium hirsutum L.), jimsonweed (Datura stramonium L.), peanut (Arachis hypogaea L.), and sicklepod [Senna obtusifolia (L.) Irwin and Barnaby] all rapidly absorbed 14 Ctrifloxysulfuron between 0 and 4 HAT, but total absorption after 72 h varied by species between 30 and 70%. By comparison, tobacco absorbed 40% of applied 14 C-imazaquin 8 d after treatment (Walls et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…foliar-applied 14 C-imazaquin basipetally (Walls et al 1993). Typically, sulfonylurea herbicides move more readily in the xylem than in the phloem (Hageman and Behrens 1984;Lycan and Hart 1999;Petersen and Swisher 1985).…”
Section: Recovery Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Imazaquin is a member of the imidazolinone herbicide family and is an ALS-inhibiting herbicide (Devine et al 1993). Walls et al (1993) also reported tobacco tolerance to imazaquin applied early POST, but unacceptable injury resulted from preplant-incorporated (PPI) treatments. Tobacco is a common rotational crop with cotton in North Carolina.…”
Section: Introductionmentioning
confidence: 99%
“…Many herbicide translocation studies demonstrated that radio-labeled herbicide appeared below and above the treated leaf and represented herbicide that was translocated out of the treated leaf (Hinz and Owen 1996;Lym 1992;Nimbal 1995;Walls et al 1993). Some snidies reported more radio-labeled herbicide in the leaf below the treated leaf than in the leaf above the treated leaf (Hinz and Owen 1996).…”
Section: Herbicide Translocation and Autoradiographic Stndymentioning
confidence: 99%